Karakteristik Kuat Tekan Buis Beton Ditinjau dari Komposisi Campuran - Endang Sri Astutik; Sri Handono Budi Prastowo; I Ketut Mahardika (Jurnal Teori dan Aplikasi Fisika, 2022)
Research has been carried out on the characteristics of the compressive strength of concrete in terms of the composition of the mixture using firewood ash and without a mixture of firewood ash. This study aims to determine the compressive strength of concrete with the addition of firewood ash and to compare the compressive strength of concrete without the addition of wood ash using different ratios of sand. The composition of the wood ash variations added were 0%, 5%, 10%, 15% and 20% of the cement mass using a ratio between cement and sand of 1:4. While the composition of buis concrete without the addition of firewood ash uses a ratio of 1:2, 1:3, 1:4, 1:5 and 1:6. Testing of the concrete buis sample was carried out at the age of 28 days. The test results showed that the compressive strength of the concrete sample with the addition of firewood ash was 18 MPa, 15 MPa, 17 MPa, 15 MPa and 13.5 MPa, respectively. While the compressive strength of concrete samples without the addition of firewood ash using different sand ratios, respectively, is 31 MPa, 20 MPa, 18 MPa, 15 MPa and 13 MPa. The results show that the more additional wood ash used, the lower the compressive strength value. While the sample without the addition of wood ash shows that the more cement used, the higher the value of the compressive strength. However, when viewed from an economic point of view, the optimal level of firewood ash addition is 10% of the cement mass with a compressive strength value of 17 MPa.